Pembrolizumab‐induced auto‐immune type‐1 diabetes in a patient with metastatic melanoma. (7th March 2018) - Reslan, Zainab; Bennett, Michael; Wong, Eugene; Jacques, Sarah; Lee, Adrian
Abstract: Background: Immunotherapy for metastatic melanoma has improved response rates and progression‐free survival significantly compared to traditional chemotherapy. However, our understanding of their unique side‐effect profile remains limited given the novelty of these treatments. Unlike traditional cytotoxic chemotherapy, immunotherapy is often associated with autoimmune‐related toxicities, including colitis, thyroiditis, pneumonitis or hepatitis. However, autoimmune endocrinopathies are much less well described. These experiences are concerning as the use of these agents is becoming more widespread in other cancer subtypes and they require very different approaches in regard to toxicity management. We report a case of pembrolizumab‐induced auto‐immune diabetes and hepatitis in a patient undergoing treatment for metastatic melanoma. Clinical details: A 79‐year‐old Caucasian man was referred by his general practitioner to the emergency department with hyperglycaemia and elevated liver function tests on a background of recurrent metastatic melanoma on pembrolizumab treatment. The patient had a long history of hypertension but no other significant past medical history. The patient did not have a personal or family history of diabetes or autoimmune disease. Outcomes: The patient was treated with a basal‐bolus insulin regimen for his new‐onset diabetes and a reducing dose of prednisolone for hepatitis. Conclusion: New emerging immunotherapy treatments are changing the outcomes of patients with metastatic melanoma; however, their side effect profile differs from traditional chemotherapeutic agents and has not been fully explored. Healthcare professionals and patients should be aware that autoimmune side effects, such as diabetes and hepatitis, do occur in the context of these new treatments.